Incorporating ObjectStab library and fuzzy logic toolbox for design of power system damping controller - Issarachai Ngamroo; Boonrat Somritvanitcha; Komsan Hongesombut (My University, 2008)
Abstract ObjectStab is a general purpose simulation tool for power system stability studies developed by Modelica which is an object‐oriented modeling language. It provides enough modeling flexibility to allow addition or modification of new power system components. This article describes an incorporated use of ObjectStab library and fuzzy logic toolbox in Matlab/Simulink to enhance the application of this library into fuzzy control design environment. The example provided here is the modeling of the static synchronous series compensator (SSSC) which is the new device developed in the ObjectStab. In addition, the interface of ObjectStab with Matlab/Simulink for an SSSC damping controller design by fuzzy logic toolbox is explained step by step. In fuzzy control design, a simple approach to extract membership functions and fuzzy logic control rules based on observed signals is presented. Simulation studies in a two‐area four‐generator power system confirm the effectiveness of the fuzzy controller of SSSC designed by the incorporated use of ObjectStab and fuzzy logic toolbox. © 2008 Wiley Periodicals, Inc. Comput Appl Eng Educ 16: 243–255, 2008; Published online in Wiley InterScience (www.interscience.wiley.com); DOI 10.1002/cae20126
Keywords: Toolbox; Modelica; Fuzzy electronics; Interface (matter); Modeling and Simulation Systems